Orientasi Kewirausahaan, Dinamika Lingkungan, dan Kemampuan Manajemen Serta Dampaknya terhadap Kinerja (Studi pada Industri Kecil Menengah Bordir di Jawa Timur) - Suci, Rahayu Puji (Universitas Brawijaya, Indonesia, 2009)
This research is conducted to investigate of entrepreneurship orientation, environment dynamic, and management skills of the entrepreneur towards performance. The research is applied to the small and middle enterprise (SME) of embroidery industries in east java which have to encounter dynamic and uncertain environment and high intensity competition and need good management skills in order to win in the competition. The population of the research is the entrepreneurs who are also the owners and managers of the small and middle embroidery industries in east java. The total samples were 314 samples taken from 5 research areas. Meanwhile, the testing of the influence of management skills variable not have an effect on improvement of performance SME.